A4NH 2018 annual report highlights: Flagship 4 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2019)
This includes three highlights document for Flagship 4 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Childcare Centers as Platforms for Agriculture and Nutrition Highlight 2: Strengthening Capacity of Nutrition Leadership Highlight 3: Culmination of Leveraging Agriculture for Nutrition in South Asia (LANSA) Work